Co-designing person-centred quality indicator implementation for primary care in Alberta: a consensus study - Kimberly Manalili; Catherine M. Scott; Brenda Hemmelgarn; Maeve O’Beirne; Allan L. Bailey; Michel K. Haener; Cyrene Banerjee; Sue P. Peters; Mirella Chiodo; Fariba Aghajafari; Maria J. Santana (Research Involvement and Engagement, 2022)
Plain English summary Person-centred care (PCC) is a model of care where patient needs and preferences are included in decisions about care and treatment. To improve PCC in primary care in Alberta, Canada, we plan to use person-centred quality indicators (PC-QIs). Using PC-QIs involves surveying patients about their care experiences and using this information to make improvements. For example, if 20% of patients do not feel they are getting enough information, the clinic may create a checklist for the providers so information is not missed. We engaged a panel of 11 people, including patients, family doctors, and staff who support quality improvement in clinics across the province to decide together which PC-QIs primary care clinics in Alberta should use. We also asked the panel to decide the most important strategies that would make using the PC-QIs more successful. The panel chose PC-QIs related to: patient and caregiver involvement in decisions about care and treatment, a trusting relationship with the healthcare provider, having health information technology to support PCC, partnering with communities in healthcare, and the patient’s overall experience. The most important strategies were: developing partnerships among people working in primary care in Alberta, discussing their needs and common efforts for improving PCC, engaging “champions,” and securing funding that would be needed. Finally, we asked the panelists to share their experiences with participating in this process. Panelists found the process useful and that their input was valued. Most panelists would also like to continue to work together to put the PC-QIs into practice.